Possibilities of use of method of capillary electorphoresis while analyzing aqueous extract from saline soils - G. I. Chernousenko; T. I. Borisochkina; N. S. Nikitina (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
A comparative analysis of anions (Cl-, SO4 2-) and cations (Ca2+, Mg2+, Na+) detection in samples of saline soils by classical methods of titration (with use of atomic absorption analyzer Kvant-2AT for Na+ detection) and by method of capillary electrophoresis on Kapel-105 was performed. An analysis has shown limits of use of these methods as well as possibility of conversion of data obtained by method of capillary electrophoresis into data that could be obtained by methods of titration and atomic absorption. It was found that results of these methods correlate worse for anions especially for chlorides and better for cations. Largest divergence was noticed in areas of extremely low or extremely high rates of soils salinity. Functional relations (mostly linear or polynomial) between magnitudes obtained by different methods was found. The use of suggested equations of conversion gives an opportunity to compare results obtained by traditional methods (titration and atomic absorption) with those obtained by the method of capillary electrophoresis.